Performance evaluation of manufacturing system using simulation / Mohd Kamal Mohd Nawawi and Razman Mat Tahar - Mohd Nawawi, Mohd Kamal; Mat Tahar, Razman (2004)
One of the largest application areas for simulation is that of manufacturing systems, with the first uses dating back to at least the early 1960's. Simulation is an analytical tool attractive to managers and engineers seeking to design, understand, and improve a business process. Simulation permits study and improvement of the process design, via use of a model, without having to build, disturb, or disable the actual process. This paper discusses how simulation is used to improve the performance of the local manufacturing plant that manufactures aircraft composite parts. In this study, simulation technique is applied to model the existing system and then used to simulate the design and operational policies of the plant production process. The model covers the operations at Primary Manufacturing Area (PMA) and Secondary Manufacturing Area (SMA). The model is built in modular form and then later integrated. The paper concludes with some material highlighting how easy the tool is to apply to this kind of problem and also presents some thoughts on how the tool might be enhanced to improve its value.